Politics of global governance : international organizations in an interdependent world - Frederking, Brian; Diehl, Paul F. (Paul Francis) (Boulder, Colorado : Lynne Rienner Publishers, Inc., 2015)
Covering decisionmaking processes, peace and security affairs, and economic, social, and humanitarian issues, The Politics of Global Governance helps students of international organizations to understand the major themes, theories, and approaches central to the subject. The fifteen new selections in this fully revised edition reflect an increased emphasis on transnational governance and emerging global norms. The editors' section introductions underscore the importance of the essays, which have been selected not only for their relevance, but also their accessibility.
Introduction / Brian Frederking and Paul F. Diehl -- Identifying Formal Intergovernmental Organizations / Thomas J. Volgy, Elizabeth Fausett, Keith A Grant, and Stuart Rodgers -- Why States Act Through Formal International Organizations / Kenneth W. Abbott and Duncan Snidal -- Introduction to Part 2 / Paul F. Diehl and Brian Frederiking -- Myths of Membership: The Politics of Legitimation in UN Security Council Reform / Ian Hurd -- Transnational Advocacy Networks in International and Regional Politics / Margaret E. Keck and Kathryn Sinkkink -- Introduciton to Part 3 / Paul F. Diehl and Brian Frederking -- Demanding Peace: The Impact of Prevailing Conflict on the Shift from Peacekeeping to Peacebuilding / Alexandru Balas, Andrew P. Owsiak, and Paul F. Diehl -- "The Responsibility to Protect": Humanitarian Concern and the Lawfulness of Armed Intervention / Christopher C. Joyner -- Targeting the Right Targets? The UN Use of Individual Sanctions / Peter Wallensteen and Helena Grusell -- A Tale of Two Institutions: The United Nations Security Council and the International Criminal Court / Rosa Aloisi -- Introduction to Part 4 / Brian Frederking and Paul F. Diehl -- International Norm Dynamics and the "End of Poverty": Understanding the Millennium Development Goals / Sakiko Fukuda-Parr and David Hulme -- The Regime Complex for Food Security: Implications for the Global Hunger Challenge / Matias E. Margulis -- Providing a Release Valve: The US-China Experience with the WTO Dispute Settlement System / Kennan J. Castel-Fodor -- Global Governance and the Spread of Cyberspace Controls / Ronald J. Deibert and Masashi Crete-Nishihata -- The Financial Crisis, Contested Legitimacy, and the Genesis of Intra-BRICS Cooperation / Oliver Stuenkel -- Is the EU Collapsing? / Wallace J. Thies -- Introduction to Part 5 / Brian Frederking and Paul F. Diehl -- The Promise and Challenge of Global Network Governanace: The Global Outbreak Alert and Response Network / Chris Ansell, Egbert Sondorp, and Robert Hartley Stevens -- Order out of Chaos: Public and Private Rules for Managing Carbon / Jessica F. Green -- Global Human Rights Monitoring, New Technologies, and the Politics of Information / Philip Alston and Colin Gillespie -- Trafficking of Women: Norms, Realities, and Challenges / Rashida Manjoo -- Reforming the United Nations: Lessons from a History of Progress / Edward C. Luck.
Includes bibliographical references and index.
Keywords: International agencies; Non-governmental organizations; International agencies; Non-governmental organizations; Global Governance